(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
With the aim of to correlate the microstructure, hardness and fracture surface with the fatigue strength of SAE 1045 steel was did this investigation. To achieve this objective, fatigue tests were performed in rotating bending to standardized specimens fatigue with different heat treatments. Three microstructures were evaluated: martensite, tempered martensite at 300°C and tempered martensite at 600 °C. The results showed a correlation between hardness and fatigue strength of the material for the microstructures tempered at 300°C and 600°C, also was confirmed that the growth of the cementite particles of material, when it was tempered of 300°C to 600°C, is the most important microstructural factor in decreasing the fatigue strength of the SAE 1045 steel. It is also observed that with the increasing of the tempering temperature the fracture mechanisms are more ductile than brittle.